MODEL OF THE RISK MANAGEMENT OF INTRODUCTION INNOVATIVE PROJECTS IN THE NUCLEAR INDUSTRY - D. Chumak (Вестник университета)
The model of risk management innovation and innovative projects in the nuclear power industry is presented. We present arguments justifying the need for the development of this model. The system of operation risk management model is considered. The model is presented in the form of the three-dimensional navigator, which together accounted for three criteria: requirements, opportunities and risks.